2017
DOI: 10.3892/ol.2017.6145
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ABCB1 in stage I lung adenocarcinoma

Abstract: Abstract. Cancer stem cell (CSC) properties have been recently proposed to explain tumor carcinogenesis and multidrug resistance in several human cancers, including non-small cell lung cancer (NSCLC). The present study examined the protein expression of three CSC-associated markers, namely ATP binding cassette subfamily B member 1 (ABCB1), aldehyde dehydrogenase 1 family member A1 (ALDH1A1) and cluster of differentiation (CD) 44, by immunohistochemistry in 194 NSCLC patients who underwent complete resection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“… 6 In addition, a number of molecular prognostic indicators have been reported in the literature. 7 9 These were examined to have association with the prognosis of stage I patients; however, only a few of them were utilized in subsequent studies. 3 Therefore, searching for potential prognostic biomarkers is necessary to gain insights into further therapeutic options for early-stage patients.…”
Section: Introductionmentioning
confidence: 99%
“… 6 In addition, a number of molecular prognostic indicators have been reported in the literature. 7 9 These were examined to have association with the prognosis of stage I patients; however, only a few of them were utilized in subsequent studies. 3 Therefore, searching for potential prognostic biomarkers is necessary to gain insights into further therapeutic options for early-stage patients.…”
Section: Introductionmentioning
confidence: 99%
“…Human ABC transporters are divided into seven (A to G) subfamilies [ 18 ]. Among them, ABCB1 is highly expressed in patients with lung adenocarcinoma and associated with poor survival [ 19 ]. ABCB1 inhibitors can overcome resistance to CDDP [ 20 ], doxorubicin (DXR, an anthracycline antibiotic) [ 21 ], and paclitaxel (a taxane-derived chemotherapeutic agent) [ 22 ], in human lung adenocarcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another study observed that ABCB1 is highly expressed in patients with stage I lung adenocarcinoma and that the expression of this protein is associated with poor survival, which indicates that ABCB1 expression is useful for predicting the prognosis of patients with lung adenocarcinoma [72]. Yang et al identified ABCB1 as a vital downstream target of the chromosomal helicase/ATPase DNA-binding protein 1-like gene in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%